Kearifan Lokal Petani Dalam Mengenal Dan Penanganan Awal Ancaman Akibat Bahan Berbahaya Di Area Pertanian - Arista Maisyaroh; Eko Prasetya Widianto; Rizeki Dwi Fibriansari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Introduction: Along with the increasing productivity of agricultural products by using sophisticated farming tools and machinery and the use of pesticides is not followed by the development of farmers' health status. Where many research results state the many effects of acute or chronic poisoning due to the use of pesticides that are not in accordance with procedures and the frequent occurrence of trauma in agricultural areas. However, research that aims to find out the gap has not been much studied; therefore, this study aims to explore the local wisdom of farmers in recognizing and handling early threats due to hazardous materials in agricultural areas. Method: The research design used was qualitative with an inductive content analysis approach with the Focus Group Discussion (FGD) method. The FGD was conducted using a semistructured question involving 2 FGD groups, each group consisting of 7 and 8 people with a background of food cropfarmers and horticultural cultivation in Lumajang Regency. Data were collected and analyzed using thematic analysis based on the Krueger, R. and Casey, M. Results : The research produced three themes, namely sharing information on sources of threats in agriculture, maintaining the tradition of farming, and utilizing the wealth of traditional medicine. Conclusion: Risk reduction due to hazardous materials in agricultural areas is more appropriate using a local wisdom-based approach. This approach will be able to produce appropriate technology products that are closer to the day-to-day experience of farmers so that they are easier to accept and apply.